2015
DOI: 10.1016/j.heares.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of middle-ear input in fluid-filled middle ears by controlled introduction of air or a novel air-filled implant

Abstract: The effect of small amounts of air on sound-induced umbo velocity in an otherwise saline-filled middle ear (ME) was investigated to examine the efficacy of a novel balloon-like air-filled ME implant suitable for patients with chronically non-aerated MEs. In this study, air bubbles or air-filled implants were introduced into saline-filled human cadaveric MEs. Umbo velocity, a convenient measure of ME response, served as an indicator of hearing sensitivity. Filling the ME with saline reduced umbo velocity by 25–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…We filled the entire mastoid cavity with fluid in order to achieve the maximum conductive loss observed in those studies, across all frequencies. A similar set of experiments in human cadaveric temporal bones showed that umbo velocities are reduced to the greatest degree at high frequencies (>1 kHz) when the ear is completely filled with fluid (10), and that this reduction may be reduced by re-introduction of air into the middle ear cavity (25). These reports suggest that changes in umbo velocity are directly related to the proportion of the middle ear filled with fluid.…”
Section: Discussionmentioning
confidence: 96%
“…We filled the entire mastoid cavity with fluid in order to achieve the maximum conductive loss observed in those studies, across all frequencies. A similar set of experiments in human cadaveric temporal bones showed that umbo velocities are reduced to the greatest degree at high frequencies (>1 kHz) when the ear is completely filled with fluid (10), and that this reduction may be reduced by re-introduction of air into the middle ear cavity (25). These reports suggest that changes in umbo velocity are directly related to the proportion of the middle ear filled with fluid.…”
Section: Discussionmentioning
confidence: 96%